1989
DOI: 10.1177/030089168907500525
|View full text |Cite
|
Sign up to set email alerts
|

In Situ and Microinvasive Carcinoma with Squamoid Differentiation Arising in a Phyllodes Tumor: Report of a Case

Abstract: A case of in situ and invasive ductal carcinoma with areas of squamoid differentiation arising in a phyllodes tumor is reported. This last aspect has never been described before and is discussed reviewing the previously reported cases in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Axillary lymph node dissection is not part of the standard treatment for phyllodes tumors as lymph node spread is rare [14]. Several authors have suggested treating carcinoma within phyllodes tumors according to the carcinomatous component [9,14]. Our case supports this view, particularly with respect to the need for assessment of axillary lymph node status in determining prognosis and treatment.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Axillary lymph node dissection is not part of the standard treatment for phyllodes tumors as lymph node spread is rare [14]. Several authors have suggested treating carcinoma within phyllodes tumors according to the carcinomatous component [9,14]. Our case supports this view, particularly with respect to the need for assessment of axillary lymph node status in determining prognosis and treatment.…”
Section: Discussionsupporting
confidence: 78%
“…This case represents the youngest age at presentation with this combination tumor. The reported subtypes include in-situ and invasive lobular and ductal (no special type) carcinoma, tubular carcinoma and squamous carcinoma [2-7,9-13]. Some authors have noticed greater atypia in epithelial components of recurrent phyllodes tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the median age of occurrence of disease is 40-50 years, and the documented literature about ductal carcinoma in situ arising in phyllodes tumor is a rare situation especially in older patients, our case illustrates that this situation can be seen in younger ages. Moreover, our case presented here is the youngest patient with ductal carcinoma in situ arising in phyllodes tumor according to documented in the literature (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 69%
“…Even this transformation is rare, most of them are infiltrative ductal carcinomas (2). Documented literature about ductal carcinoma in situ arising in phyllodes tumor is a rare situation (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). We report a 19-year old patient who was diagnosed with ductal carcinoma in situ arising in a benign phyllodes tumor of the breast.…”
Section: Introductionmentioning
confidence: 99%